Mail-in-rebate coupled with revenue sharing and downward direct discount for supply chain coordination. (2015) - Saha, Subrata; Panda, Shibaji; Modak, Nikunja Mohan; Basu, Manjusri
Use of sales promotion in the short-term to increase sales by revenues and market share for slow-moving items is common in the supply chain, though in such cases performances of chain members are suboptimal. On the contrary, a growing body of literature suggests that a high degree of integration is needed to optimise performances of all supply chain partners simultaneously. To address supply chain integration, when sales promotion is used, we consider a three-echelon supply chain. Demand depends on the selling price by the retailer and individual promotional mechanisms are chosen by channel members. We study game theoretical models to examine impacts of two promotional policies, e.g., mail-in-rebate (MIR) and downward direct discount (DDD) on supply chain coordination. Effectiveness and flexibility of MIR, MIR coupled with revenue sharing (RS) and DDD as coordination contracts are discussed analytically. We show that in decentralised decision making all channel members prefer manufacturers MIR and discard the possibility of distributers' MIR. Although to cut out channel conflict all chain members cooperate actively by complementing one another through contribution to invariant discount that is provided to customers, still, distributors and manufacturers prefer MIR and RS to DDD, whereas retailers prefers the reverse.